1999
DOI: 10.1046/j.1524-4725.1999.08240.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study Evaluating Topical Onion Extract as Treatment for Postsurgical Scars

Abstract: Scar hydration is an important factor in wound healing and can be achieved with topical petrolatum-based ointment. Topical onion gel extract was ineffective in improving scar erythema and pruritus in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 15 publications
(18 reference statements)
0
38
0
Order By: Relevance
“…The combined effects of the CAH mixture show time-related differences. The drug reduces inflammation and fibroblast proliferation in the first stage and decreases the accumulation of connective tissue elements such as proteoglycans and collagen in the terminal stages of the wound healing process (21,23). It has therefore been used for many years to achieve a hypertrophic scar-free wound healing process (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of the CAH mixture show time-related differences. The drug reduces inflammation and fibroblast proliferation in the first stage and decreases the accumulation of connective tissue elements such as proteoglycans and collagen in the terminal stages of the wound healing process (21,23). It has therefore been used for many years to achieve a hypertrophic scar-free wound healing process (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…21 However, limited clinical trials have failed to demonstrate any clinical improvement in scar height or erythema. 22 Products containing onion extracts did not provide any additional improvement in scar cosmesis than a petrolatum-based ointment. 23 Hosnuter et al 24 evaluated the therapeutic activity of topical onion extract in gel form to treat hypertrophic scars and keloids.…”
Section: Onion Extractmentioning
confidence: 92%
“…106 There was also no benefit seen with Mederma in a trial involving human patients following Mohs microsurgery. 107 The drug imiquimod modulates the inflammatory response in wound healing and stimulates interferon activity. 101 Several noncontrolled studies evaluated the use of imiquimod cream after surgical excision of keloids and reported a wide range of recurrence rates (0-100%).…”
Section: Stem Cells In 2009 Biernaskie Et Al Deter-mentioning
confidence: 99%